Proteinuria and Hematuria in the Neonate - Joseph, Catherine (Curr Opin Pediatr, 2016)
PURPOSE OF REVIEW: Neonatal proteinuria and hematuria while not common can have potentially devastating consequences if left undiagnosed and untreated. It is important to distinguish between inherited and acquired causes of proteinuria to initiate appropriate and timely treatment. In regards to hematuria, it is critical to identify true hematuria from pseudo-hematuria in order to balance between thorough investigation and unnecessary laboratory work up. This review provides an overview of the common causes of hematuria and proteinuria in a neonate. RECENT FINDINGS: Identification of genetic mutations in nephrotic syndrome has improved our understanding of the role of various proteins that play an important role in maintaining the glomerular filtration barrier. With the advancement in our ability to provide care for extreme premature neonates, the incidence of acute kidney injury has increased in these neonates along with proteinuria and hematuria. SUMMARY: Persistent proteinuria after neonatal acute kidney injury would be of interest in regards to the risk of developing future chronic kidney disease and hypertension.